Collaborative Governance Model In The Development Of Tourism In Ciamis District (Journal of Namibian Studies : History Politics Culture, 2023)
This research is motivated by the ineffectiveness of tourism development which is characterized by actor mindset, low level of coordination, limited budget availability, inadequate accessibility and infrastructure, minimal human resources (HR), implementation of technical regulations governing stakeholder involvement is not technically optimal and low support. and the commitment of all tourism stakeholders in developing tourism in Ciamis Regency. The research method used is a qualitative method (qualitative research) with a case study approach. Data collection techniques were carried out through literature study, documentation, observation, FGD, interviews and analysis techniques using data triangulation. The results of the research reveal that the collaborative governance model in effective tourism development in Ciamis Regency is by identifying institutional actors and stakeholders, optimizing coordination and clarity of collaborative Standard Operating Procedures (SOP), conducting discussions and brainstorming as well as carrying out massive socialization which is supported with aspects of local wisdom as strengthening and novelty of research on collaborative governance models in tourism development in Ciamis Regency.